External stress-free reversible multiple shape memory polymer enabled by using broad melting range as equivalent multiple switching phases. (February 2023) - Huang, Yanan; Dang, Guiqing; Zhu, Min; Fan, Longfei; Rong, Minzhi; Zhang, Mingqiu
Highlights: Crystals with broad melting range can act as equivalent multiple switching phases. Reversible multiple shape memory polymer is successfully prepared. Record-high number of temporary shapes have been memorized. The trained sample can freely deform to the desired shapes by varying temperature. Abstract: Because the reversible shape memory polymers developed so far can only morph among the original shape and two or less temporary shapes, the corresponding deformations have to be step-like accordingly, which is inappropriate for fine regulation of smart mechanisms like soft robots and actuators. To overcome the drawback, the authors of the present work developed a novel external stress-free reversible multiple shape memory crosslinked polyurethane (PU), in which the crystalline region that possessed a broad melting temperature range served as the equivalent multiple switching phases and the inter-/intra-macromolecular hydrogen bonding networks as the internal stress provider. After the thermal programming under stretching, the crystalline phase of the PU practically memorized quite a few temporary shapes. By sequentially activating partial melting of the crystalline region of the trained PU at different melting temperatures during heating, the fixed temporary shapes successively returned to the original shape. Moreover, the above process can be reversed by initiating partial re-crystallization at different temperatures during cooling. Since the activation and recovery temperatures can be optionally selected, the same programed PU successfully implemented reversible triple, quadruple and quintuple shape memory effects. The simple synthesis for constructing broad melting temperature range via copolymerization of identical semicrystalline polymers with various molecular weights as well as the record-high number of memorized temporary shapes may promote application of reversible shape memory polymers. Graphical abstract: Image, graphical abstract